PENGARUH LAGU RELIGI ISLAM DALAM INDUSTRI MUSIK: TINJAUAN FENOMENOLOGI TERHADAP BAND LOKAL MALWAPATIH: Tinjauan Fenomenologi Terhadap Band Lokal Malwapatih - Islam, Ana Ul; Prastio, Yana Leo; Bahiroh, Sana; Aiswara, Anisa; Ariansah, Ariansah (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2023)
This research will explain the music industry in Purwokerto. To obtain research data that can be accounted for, researchers carry out various steps and methods in obtaining data, including: 1) Observation, 2) In-depth interviews, 3) Data collection, 4) Data analysis and reduction. The aim of this research is to explain Islamic religious music and its influence on music industry activists and fans within the scope of a local band called Malwapatih. The researcher used the phenomenological theory of Alfred Schutz, and used a qualitative descriptive method which was carried out by in-depth interviews with sources, namely Malwapatih band personnel. The results of this research include: 1) Band members tend not to question these differences, and view differences as natural, just respect each other's differences of opinion regarding whether music is halal or haram. 2) The Islamic religious music industry has various influences on society, especially music industry activists, as well as fans of the industry. The influence of the music industry for its activists can provide additional income besides their main job, and Islamic religious music can be a tool to get closer to Allah SWT. Meanwhile, for those who enjoy it, listening to Islamic religious songs can also soothe the heart and soul. 3) The benefits of religious songs are as a means of getting closer to Allah SWT and increasing your love for the Prophet, through the lyrics of the song.